Kernel-based control of persistent web server connections. - Voigt, Thiemo
Several overload admission control architectures have been developed to protect web servers from overload. Some of these architectures base their admission decision on information found in the HTTP header. In this context, persistent connections represent a challenging problem since the HTTP header of the first request does not reveal any information about the resource consumption of the requests that might follow on the same connection. In this paper, we present an architecture that prevents uncontrollable server overload caused by persistent connections. We evaluate our approach by various experiments.